Safety profile of vascular endothelial growth factor receptor tyrosine-kinase inhibitors in pediatrics: a pharmacovigilance disproportionality analysis - Xue, Yifei; Feng, Shuo; Li, Guangyao; Zhang, Chao (Frontiers in Pharmacology, 2023)
Introduction: existing research on children consists primarily of phase I/II clinical trials for VEGFR-TKI. System reports of safety on the use of VEGFR-TKI in pediatrics are lacking. Aim: to investigate the safety profiles of VEGFR-TKI in pediatrics via the FDA Adverse Event Reporting System (FAERS). Method: data regarding VEGFR-TKIs were extracted from the FAERS between 2004Q1 to 2022Q3 and categorized by the Medical Dictionary for Regulatory Activities (MedDRA). Population characteristics were analyzed, and reporting odds ratio (ROR) was performed to identify risk signals associated with VEGFR-TKI. Results: 53 921 cases containing 561 children were identified in the database from May 18, 2005, to September 30, 2022. Among those in the system organ class, skin, subcutaneous tissue disorders, and blood and lymphatic system disorders in pediatrics contributed to over 140 cases. Palmar-plantar eythrodysesthesia syndrome (PPES) in VEGFR-TKI presented the most significant 340.9 (95% 229.2-507.0). And pneumothorax also gave a high ROR of 48.9 (95% 34.7-68.9). For a specific drug, musculoskeletal pain gave a ROR of 78.5 (95% 24.4-252.6) in cabozantinib and oesophagitis in lenvatinib with a ROR of 95.2 (95% 29.5-306.9). Additionally, hypothyroidism presented a high signal, especially sunitinib, with a ROR of 107.8 (95% 37.6-308.7). Conclusion: the present study explored the safety profile of VEGFR-TKI in pediatrics using the FAERS database. Multiple skin and subcutaneous tissue disorders, as well as blood and lymphatic system disorders, were common VEGFR-TKI-related AEs in SOC. No serious hepatobiliary AEs were detected. For the specific AEs, PPES and pneumothorax were VEGFR-TKI-related AEs that presented significantly higher signals than those in the general population.